2019
DOI: 10.1002/ange.201907245
|View full text |Cite
|
Sign up to set email alerts
|

Evolvierte aliphatische Halogenasen ermöglichen die regiokomplementäre C‐H‐Funktionalisierung einer hochwertigen Chemikalie

Abstract: Nicht-Häm-Eisen(II)-Halogenasen sind wertvolle Biokatalysatoren fürd ie stereo-und enantioselektive Halogenierung von nicht-aktivierten sp 3 -Kohlenstoffatomen. Das Substratspektrum dieser Enzyme ist jedocheng auf natürliche Substrate beschränkt. Hier haben wir die Halogenase WelO5* zur Chlorierung eines pharmazeutisch interessanten Martinellin-Fragments verändert. Durch Evolution konnten wir eine Halogenase entwickeln, die eine mehr als 290-fachh çhere katalytische Produktivitätu nd 400-fachh çhere scheinbare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Turning to nature, the use of Fe/a-ketoglutarate-dependenth alogenases may offer av iable strategy toward the asymmetrich alogenation of unactivated CÀH bonds.F irst members of this family acting on freestanding substrates have been discovered and pioneering protein engineering studies suggest that the substrate scope of freestanding aKGHs can be more easily broadened than anticipated. [34,37] Nevertheless, the young field hast ot ackle ar ange of remaining challenges to bring Fe/a-ketoglutarate-dependent halogenases to their full potential. Most important will be to increase the low turnover number of the short-lived aKGHs, which likely suffer from autoxidation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Turning to nature, the use of Fe/a-ketoglutarate-dependenth alogenases may offer av iable strategy toward the asymmetrich alogenation of unactivated CÀH bonds.F irst members of this family acting on freestanding substrates have been discovered and pioneering protein engineering studies suggest that the substrate scope of freestanding aKGHs can be more easily broadened than anticipated. [34,37] Nevertheless, the young field hast ot ackle ar ange of remaining challenges to bring Fe/a-ketoglutarate-dependent halogenases to their full potential. Most important will be to increase the low turnover number of the short-lived aKGHs, which likely suffer from autoxidation.…”
Section: Discussionmentioning
confidence: 99%
“…To wards this goal, structural studies of substrate-bound WelO5* and Wi-WelO15 variantso nt he evolutionary trajectory toward their tailoredp rogeny may shed some light on this aspect of the enzyme's structure-function relationship as the amount of hydroxylated product produced by the halogenases significantly drops in the course of evolution. [34,37] To day,F e/a-ketoglutarate-dependenth alogenases may already be applied for the synthesis of compounds that can be used in structure-activity relationship (SAR) studies. [63] Looking forward, the introduction of aKGHs into biosynthetic pathways, analogously to studies carried out with flavin-dependent halogenases, [47a, 64] mayb ea na ttractive tool to increaset he diversity of accessible products and to synthesize bioactive molecules or valuable intermediates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[78] Computational studies revealed that such interactions can channel the reaction towards cleavage of the less favourable CÀHb ond,a so bserved forp rolyl 4-hydroxylase [79] and flavonol synthase, [73] or guide the order of reactions, as in the case of the ergothioneine biosynthesis enzyme EgtB. [80] The introductiono famutation within the second coordination sphere can alter the regio-and stereoselectivity of the reaction, as was demonstrated in mutagenesisstudies of the halogenase WelO5* [81] and PhrA. [22] Ta ken together,i ts eems that the key to hydroxylation is maintaining the interactions that stabilise the enzyme-substrate complex, whereas desaturation is hindered by the necessity to break favourable interactions to re-positiont he substrate-derived radicala nd provide properc ontact between the abstracted hydrogen andt he Fe III ÀOH moiety.…”
Section: Desaturation Of Dgpc Has Never Been Observedmentioning
confidence: 92%